Wide bandgap semiconductor conversion devices for radioisotope microbatteries. (May 2022) - Lioliou, G.; Krysa, A.B.; Barnett, A.M.
Abstract: Five mesa p + -i-n + photodiodes (each of 0.126 mm 2 area) were investigated as conversion devices for X-ray-voltaics, in order to understand the comparative effects between different semiconductor materials, device structures, and X-ray incident power, and to explore them for use in future radioisotope microbatteries. Three semiconductor materials (AlInP, InGaP, and GaAs) and three i layer thicknesses of one material, AlInP (2 μm, 6 μm, and 10 μm), were investigated under the illumination of various controlled X-ray incident powers. The highest short circuit current was achieved with the GaAs device due to its thickest active layer and highest linear absorption coefficients at the most numerous incident X-ray photon energies (Mo Kα at 17.48 keV; Mo Kβ at 19.6 keV). The highest open circuit voltage was achieved with the 10 μm AlInP device due to its widest bandgap (cf. InGaP and GaAs) and its highest short circuit current (cf. the 2 μm and the 6 μm AlInP devices). The greatest output X-ray power was recorded with the InGaP device due to its highest fill factor (i.e. relatively low series and high shunt resistance) compared to the rest of the devices, although the GaAs device had the highest theoretical output X-ray power. A method for selecting the most suitable semiconductor material and device structure of conversion devices for radioisotope microbatteries (for exhibiting the highest power output) is presented considering the incident X-ray spectrum, while highlighting the importance of non-ideal device effects (reduced charge collection efficiency, increased series resistance, and reduced shunt resistance).